Effect of Tobacco Stem Treated by Steam Explosion on the Release of Harmful Chemicals in Cigarette Smoke - Xue, Fang; Li*, Dongliang; Feng, Guanglin; Song, Guangfu (Asian Journal of Chemistry, 2014)
This paper reported steam explosion technology to treat tobacco stem. The tobacco stem was then added to the tested tobacco shred in appropriate proportion to observe how tobacco stem after steam-explosion treatment affects harmful chemicals in cigarette smoke such as tar, nicotine, CO, phenol and benzo[a]pyrene. The results showed that with the increase of the addition of tobacco stem, the contents of phenol, benzo[a]pyrene, tar and nicotine in cigarette mainstream smoke dropped. Compared with blank samples, the highest drop of phenol, benzo[a]pyrene, tar and nicotine was 36.50, 36.63, 28.99 and 38.46 %, respectively; On the condition that there was no influence on cigarette burning, the addition of tobacco stem treated by steam explosion can be increased to at most 25 % as tobacco shred substitute.